Students’ Multicultural Perspective in Project Based Learning Method - Murtiyanto, Rizky Kurniawan; Rahmawati, Rizka; Hasan, Halid; Kristianingsih, Tatiana (Jurnal Ijtihad, 2024)
Students perception is something that crucial to be understood by educators in order to shape a suitable appraches to use in class so the expected outcomes can be achieved. In responding to the recommedatioon of method that can be used in higher education level is Project Based Learning (PBL). This method concerns to activities that more students’ center and the process how the students providing solutions of the real problem faced by the industry or people in general by implementing their knowledge and critical thinking. So, this study is aimed to see how the students’ perceptions of the implementation of PBL in their classrooms. This study applied the descriptiove qualitative method by describing phenomena. Based on the questionnaire and interview done, it is found out that overall students have good perceptions toward the implementation of PBL, though there are some lacks related to the role of the educators and also the collaborative working among team members.